Isolation and Characterization of a Novel Lytic Phage N22 and Its Effect on Drug-Resistant Klebsiella Pneumoniae - Liu D; Qin K; Hong C; Huang W; Li W; Lian P; Li M; Chen H; Liu X (Infection and Drug Resistance)
Dongyu Liu,1,* Kunhao Qin,2,* Chengying Hong,1 Wei Huang,3 Wei Li,1 Puqiao Lian,1 Mengyao Li,1 Huaisheng Chen,1 Xueyan Liu1 1Department of Critical Care Medicine, Shenzhen People’s Hospital, The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, 518020, People’s Republic of China; 2Jiangxi Province Key Laboratory of Organ Development and Epigenetics, Clinical Medical Research Center, Affiliated Hospital of Jinggangshan University, Medical Department of Jinggangshan University, Ji’an, 343009, People’s Republic of China; 3Department of Laboratory Medicine, Shenzhen People’s Hospital, The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, 518020, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xueyan Liu, Department of Critical Care Medicine, Shenzhen People’s Hospital, The Second Clinical Medical College, Jinan University; The First Affiliated Hospital, Southern University of Science and Technology, Shenzhen, Guangdong, 518020, People’s Republic of China, Email 13554843721@163.comBackground: Klebsiella pneumoniae (KP) infections present a significant clinical challenge and are frequently associated with elevated drug resistance. The use of phage therapy has resurged in response to escalating antibiotic resistance. This study aimed to address the multidrug resistance crisis in intensive care units by exploring the use of ceftazidime/avibactam (CAZ/AVI), a widely used clinical antimicrobial agent, in conjunction with phage therapy.Materials and Methods: We screened a clinical strain of KP from ICU and successfully isolated phage N22 from hospital wastewater. We conducted an in-depth analysis of the physiological and biochemical properties of phage N22 and determined its optimal multiplicity of infection with the clinical KP strain. The inhibitory effects of phage N22 in combination with CAZ/AVI on biofilm formation were investigated. Comparative efficacies of these combinations were evaluated using a Galleria mellonella (G. mellonella) model.Results: Phage N22 inhibited KP biofilm formation. The impact of varying phage N22 concentrations when used alongside CAZ/AVI was examined, and the combination of phage N22 and CAZ/AVI was more effective against KP than CAZ/AVI alone.Conclusion: This study provides a preliminary investigation into the effects of combining CAZ/AVI with phage therapy, highlighting its potential significance in developing novel therapeutic strategies for bacterial infections resistant to CAZ/AVI. The findings underscore the importance of advancing highly effective phage agents as alternative treatment modalities for patients with infections refractory to conventional antibiotics.Keywords: phage therapy, drug-resistant, Klebsiella pneumoniae, ceftazidime/avibactam